PROTOZOARIOS SANGUINEOS DE LAS AVES - BELTRAN, ENRIQUE (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
Describes the pachydonta pelecypod, Toucasia mexicana This and the other fossils (some of which are listed) collected in the marine sediments of the region prove that the beds are of Middle Cretaceous age, perhaps Middle Albian
AN ESC NAC CIENC BIOL
Keywords: PROTOZOARIOS SANGUINEOS, AVES; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; GENETICA ANIMAL